Persepsi Guru-Guru Sejarah SMA N 2 Kota Payakumbuh terhadap Implementasi Kurikulum 2013 - Destel Meri (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
This study aims to determine the perception of history teachers of the implementation of the 2013 curriculum in history subjects. This type of research is descriptive evaluation. From the results of the study it can be seen that in general the teacher's perception of history is positive. Although there are still shortcomings, the shortcomings will be covered over time. The conclusion of this research This is said to be positive because the 2013 curriculum according to the teacher is in accordance with the demands of his era where students are required to be more active and the task of the teacher is only as a facilitator using a scientific approach, in addition to the higher appreciation of history marked by added hours for historical subjects, which are usually only 2 hours a week in the 2013 curriculum into four hours of study and history is also grouped into two namely compulsory history which learns about Indonesian history and history of specialization ie for students who choose the Social Sciences program. Keywords: Perception, Teacher, Kurukulum 13